AMICO galaxy clusters in KiDS-DR3: cosmological constraints from large-scale stacked weak lensing profiles - Giocoli, Carlo; Marulli, Federico; Moscardini, Lauro; Sereno, Mauro; Veropalumbo, Alfonso; Gigante, Lorenzo; Maturi, Matteo; Radovich, Mario; Bellagamba, Fabio; Roncarelli, Mauro; Bardelli, Sandro; Contarini, Sofia; et al. (Astronomy and astrophysics, 2021)
Context. The large-scale mass distribution around dark matter haloes hosting galaxy clusters provides sensitive cosmological information. Aims. In this work we make use of a large photometric galaxy cluster sample, constructed from the public Third Data Release of the Kilo-Degree Survey, and the corresponding shear signal, to assess cluster masses and test the concordance Λ-cold dark matter (ΛCDM) model. In particular, we study the weak gravitational lensing effects on scales beyond the cluster virial radius, where the signal is dominated by correlated and uncorrelated matter density distributions along the line of sight. The analysed catalogue consists of 6962 galaxy clusters, in the redshift range 0.1 ≤ z ≤ 0.6 and with signal-to-noise ratios higher than 3.5. Methods. We perform a full Bayesian analysis to model the stacked shear profiles of these clusters. The adopted likelihood function considers both the small-scale one-halo term, used primarily to constrain the cluster structural properties, and the two-halo term, that can be used to constrain cosmological parameters. Results. We find that the adopted modelling is successful in assessing both the cluster masses and the total matter density parameter, ΩM, when fitting shear profiles up to the largest available scales of 35 Mpc h−1. Moreover, our results provide a strong observational evidence of the two-halo signal in the stacked gravitational lensing of galaxy clusters, further demonstrating the reliability of this probe for cosmological studies. The main result of this work is a robust constraint on ΩM, assuming a flat ΛCDM cosmology. We get ΩM = 0.29 ± 0.02, estimated from the full posterior probability distribution, consistent with the estimates from cosmic microwave background experiments.